2015
DOI: 10.1016/j.expneurol.2015.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion tensor imaging and myelin composition analysis reveal abnormal myelination in corpus callosum of canine mucopolysaccharidosis I

Abstract: Children with mucopolysaccharidosis I (MPS I) develop hyperintense white matter foci on T2-weighted brain magnetic resonance (MR) imaging that are associated clinically with cognitive impairment. We report here a diffusion tensor imaging (DTI) and tissue evaluation of white matter in a canine model of MPS I. We found that two DTI parameters, fractional anisotropy (a measure of white matter integrity) and radial diffusivity (which reflects degree of myelination) were abnormal in the corpus callosum of MPS I dog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 25 publications
(28 reference statements)
1
18
0
Order By: Relevance
“…Given that the ex vivo FA and RD changes in canines affected with MPS are similar to those found in vivo, 11,14 ex vivo imaging appears to show promise as a method for more definitive determination of alterations in the MPS brain. Furthermore, ex vivo imaging provides a means for more direct comparison between imaging findings and histological changes because images from MR scans can be co-registered with anatomical brain slices.…”
Section: Discussionmentioning
confidence: 92%
“…Given that the ex vivo FA and RD changes in canines affected with MPS are similar to those found in vivo, 11,14 ex vivo imaging appears to show promise as a method for more definitive determination of alterations in the MPS brain. Furthermore, ex vivo imaging provides a means for more direct comparison between imaging findings and histological changes because images from MR scans can be co-registered with anatomical brain slices.…”
Section: Discussionmentioning
confidence: 92%
“…Mice heterozygous for MPS I have lower than wild‐type iduronidase enzymatic activity, but have no known MPS phenotype. In addition, MPS I dogs show reduced expression of myelin‐related genes compared to heterozygote controls both at older ages (21 months; Provenzale et al, 2015) and at 7 weeks (unpublished). We were not able to study mice older than 50 weeks, as this is essentially the end of the lifespan for MPS I mice.…”
Section: Discussionmentioning
confidence: 94%
“…We found a subtler alteration in myelin composition in MPS I mice compared to those we had found in MPS I dogs. Our previous work in MPS I dogs showed reduced fractional anisotropy and loss of volume in corpus callosum, elevated cholesterol, reduced levels of myelin basic protein, and reduced expression of myelin‐related genes (Provenzale et al, 2015; Vite et al, 2013). In our canine study, we had extracted myelin from the corpus callosum white matter for compositional analysis.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Attention was chosen as previous studies have found abnormal attentional function in MPS disorders [15] , [16] , [17] . It has been hypothesized that attention is related to white matter abnormalities in MPS conditions [18] . Overall, attention scores were below the average range for the d prime, omission errors, and variability for all three groups.…”
Section: Discussionmentioning
confidence: 99%